As the crow flies ebook - Johnson, Craig (Walt Longmire Mystery, 2012)
The eighth Longmire novel from New York Times bestselling author Craig Johnson The hit drama Longmire is now streaming on Paramount+ Wyoming sherriff Walt Longmire doesn't have time for cowboys and criminals. His daughter, Cady, is getting married in two weeks, and the wedding locale arrangements have just gone up in smoke signals. Fearing Cady's wrath, Walt and his old friend Henry Standing Bear set out for the Cheyenne Reservation to find a new site for the nuptials. But their expedition ends in horror as they witness a young Crow woman plummeting from Painted Warrior's majestic cliffs. Is it a suicide, or something more sinister? It's not Walt's turf, but he's coerced into the investigation by Lolo Long, the beautiful new tribal police chief.